Transpersonal psychosomatic therapy method as a way to correct physical and psychological health of a person - Sabadukha Олексій (Psychosomatic Medicine and General Practice, 2019)
The theoretical basis of the mechanism of occurrence and passing of psychosomatic disorders has been formulated in the article. Also, there is the author’s approach in psychosomatic work proposed – a method of transpersonal therapy that allows to correct simultaneously both physical and psychological state of a person. It is shown that the conscious experience of destructive thoughts, emotions and feelings can cause functional disorders of the inner organs, which, in turn, determines cramps and stagnant processes in different parts of the body (representative areas by Zakharyin – Ged). The method of self-transpersonal psychosomatic therapy is characterized as a synthesis of bodily, psychological and spiritual practices and the result of which is the purification of a human’s psyche from destructive settings, emotions and feelings. It is helpful in the formation of a constructive attitude towards oneself, others and social conditions of life, as well as the correction of the functional state of the organism. The method is based on Victor Frankl’s logotherapy and psychophysiological studies by A. Corb. The psychotherapeutic effect of the method of transpersonal psychosomatic therapy is provided by a therapeutic massage (therapeutic, sedative) and by two psychological exercises: "Self-distancing", "Self-transcendence". Self-distancing is characterised as a person’s ability to rise above psychological problem, decreasing or getting rid of its negative influence as a result. It’s proved that this is possible due to a sense of humour and the acceptance of the psychological problem. Self-transcendence is defined as the ability of a person to go beyond destructive attitudes to new constructive values and meanings; as the ability of a person to move beyond its Self and to be directed at something or someone (a significant object or subject). It is substantiated that activating the prefrontal cortex and calming the limbic system is a necessary condition for the restoration of psychological and physical health of a person, and the method of transpersonal therapy is just directed at this. In a state of activity, the prefrontal cortex (conscious) can control the impulses of the striatum (the physical base of the subconscious), which is a condition of spiritual development of a human to a level of a person.